Milk yield and milking characteristics in Murrah buffaloes submitted to machine milked with or without calf - Couto, Alberto de Gusmao; Ramos, Alcides de Amorim [UNESP]; Sampaio, Elizabeth; Couto, Janira Lucia Assumpção; Negrão, João Alberto; Appuhamy, Jayasooriya; Mendes, Patricia; Beelen, Guimarães (Int Buffalo Information Ctr, 2013)
This work was carried out on a Murrah breed buffalo farm located in São Luiz do Quitude, Alagoas, Brazil. The objective was to compare the milk yield and milking characteristics between buffaloes machine milked with or without calf. Eighteen buffaloes used in the experiment were in their second to fourth lactation, having body weights of 650 ± 100 kg and a total milk yields of 2,127.47 ± 462.99 in the previously lactation. The animals were randomized in two treatments: system 1) machine milking without calf and system 2) machine milking with calf. Each animal attended the experiment in the day of parturition and data were collected every five days, from day 20 to day 45 of experiment. The data consisted in milk yield, milk letdown time, milking time, milk yield per milking, milk flow rate and cortisol. The milking system did not affect milk yield (P> 0.05), which showed a a day mean of 9.259 ± 1.228 kg, with 5.248 ± 1.228 kg ± 4.200 in the morning and 0.950 kg in the afternoon milking. The milk letdown time varied (p <0.05) between 1.55 min, in the group without suckling calves to 3.42 minutes in the system without suckling calves. However The milking system did not affect the total time of milking or the amount of residual milk, that was, on average, 9.81 ± 2.35 minutes and 165 g (3.88%), respectively. The cortisol level in the milk, although low, was higher in buffaloes milked with calf at foot (0.22 mg/dl vs 0.14 mg/dl). The management of buffaloes allowed the milking machine without suckling calves with no differences in daily milk production.
Keywords: Buffaloes; Milking time